2018
DOI: 10.4028/www.scientific.net/kem.777.446
|View full text |Cite
|
Sign up to set email alerts
|

Failure Observation of 3D-Printed Thrust Bearing Specimens at Cross Section Observations in Dry Conditions

Abstract: 3D printing methods are developing and they have become popular recently. 3D printing can easily make complex and seamless parts, however, there are questions about their strength. In particular, the strength of the places where the lamination layer joins is important. We performed rolling contact fatigue (RCF) tests in dry conditions using 3D-printed bearing race and observed the fracture behavior and cracks. We found that the main crack is related to the stress moving direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Figure 1 shows a schematic illustration of the lamination method. The explanation of the directions are the same as in our previous works [3][4]. The machine has a line nozzle which makes a thin layer.…”
Section: Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows a schematic illustration of the lamination method. The explanation of the directions are the same as in our previous works [3][4]. The machine has a line nozzle which makes a thin layer.…”
Section: Specimensmentioning
confidence: 99%
“…In our previous studies, we focused on the effect of the lamination direction on the development of fractures in bearing specimens [3][4]. From these investigations, we observed that the crack propagation started from small artificial defects and concluded that the crack propagation is not related to the lamination direction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigating the effects of a defect in the outer race on the vibration behavior of the ball bearing produced with a 3D printer and its lifetime is essential for ball bearing and the performance evaluation of 3D printers. In literature, although many researchers have focused on production methods and production parameters of 3D ball bearings (Harikrishnan and Soundarapandian, 2018;Mizobe et al, 2019;Mizobe et al, 2018;Lee et al, 2018aLee et al, , 2018b, there is no comprehensive study about the lifetime of 3D-printed ball bearings with outer race defects. This study investigated the effect of an outer race defect on the vibration characteristics of a polymer hybrid ball bearing manufacturing with a 3D printer and its lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers used the 3D printing method to manufacture ball bearings (Panda and Panda, 2018). They investigated the effects of the manufacturing method on the ball bearing characteristics, such as roughness, hardness and friction performance of a ball bearing produced with AM (Harikrishnan and Soundarapandian, 2018;Mizobe et al, 2019;Mizobe et al, 2018;Lee et al, 2018aLee et al, , 2018b. Mizobe et al analyzed the friction performance of 3D-printed ball bearing produced with the MultiJet Printing (MJP) method under dry and wet conditions (Mizobe et al, 2019; The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/0036-8792.htm et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation